A MECHANISM FOR THE PRODUCTION OF HYDROXYL RADICAL AT SURFACE DEFECT SITES ON PYRITE - Borda M.J.; Elsetinow A.R.; Strongin D.R.; Schoonen M.A. (My University, 2003)
A previous contribution from our laboratory reported the formation of hydrogen peroxide (H2O2) upon addition of pyrite (FeS2) to O2-free water. It was hypothesized that a reaction between adsorbed H2O and Fe(III), at a sulfur-deficient defect site, on the pyrite surface generates an adsorbed hydroxyl radical (OH*). =Fe(III) + H2O(ads) -> =Fe(II) + OH*(ads) + H+The combination of two OH* then produces H2O2. In the present study, we show spectroscopic evidence consistent with the conversion of Fe(III) to Fe(II) at defect sites, the origin of H2O2 from H2O, and the existence of OH* in solution. To demonstrate the iron conversion at the surface, X-ray photoelectron spectroscopy (XPS) was employed. Using a novel mass spectrometry method, the production of H2O2 was evaluated. The aqueous concentration of OH* was measured using a standard radical scavenger method. The formation of OH* via the interaction of H2O with the pyrite surface is consistent with several observations in earlier studies and clarifies a fundamental step in the oxidation mechanism of pyrite.